ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF ISOLATED ALLICIN (PART SECOND - F.REHMAN; SAMYA MAIRAJ (International Journal of Pharma and Bio Sciences, 2015)
The pharmaceutical importance of Allium Sativum is due to the presence of carbohydrate, protein, vitamins, essential metal and organosulpher compounds. Allicin is one of the active ingredients of freshly crushed garlic homogenates and showed a wide spectrum activity. The antimicrobial activity of different concentration of allicin against gram positive and gram negative bacterial isolate was studied by standard protocols. The maximum zone of inhibition has been observed in S. typhi and mimimum for E. Coli. Alternaria alternata has been shown maximum percentage of inhibition while minimum for Aspergillus niger. The minimum inhibitory concentration (MIC) varies bacteria to bacteria and fungus to fungus respectively. The effect of time, temperature and pH were also studied. The antibacterial efficacy was maintained at room temperature for maximum one week and maintains for longer time only at low temperature. Antimicrobial activity of garlic come from allicin, is mainly due to S-S and S-O bond which has the ability to react with thiol containing enzyme to form S-thiolation product, the broad spectrum antimicrobial effects of allicin is due to the multiple inhibitory effects on various thiol dependent enzymatic systems. The results indicate that allicin has antimicrobial activity.